The role of government institutions, social institutions and public space in forming community character - Taufik, Muhamad; Hasanah, Aan; Arifin, Bambang Syamsul (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
The purpose of this study is to examine how the character education form is being implemented in society with a particular emphasis on the function of governmental, social, and public institutions. In this study, we use the qualitative research method with a literature study approach to better understand the role that public spaces, social organizations, and governmental bodies play in character education and how that role affects the development of good character in society. This study explores the perspectives of many stakeholders in the application of character education bentuks in society using data collection approaches from various documentations, including journals and document analysis. It is anticipated that this study's findings will help people better comprehend the significance of the role that governments play in society. The study emphasizes the crucial role of active involvement from government institutions, social institutions, and public spaces in shaping good character in society. The research results are expected to provide a profound understanding of the positive impact that can result from the active engagement of these entities. Thus, the research aims to fill knowledge gaps related to the implementation of community-based character education. The conclusion of this research reflects the urgency of collaborative efforts between the government, social institutions, and public spaces in shaping positive character values, ultimately enhancing the overall quality of life in society.Penelitian ini bertujuan untuk menyelidiki implementasi bentuk pendidikan karakter berbasis masyarakat, dengan fokus pada peran institusi pemerintah, institusi sosial, dan ruang-ruang publik. Metode penelitian kualitatif dengan pendekatan analisis deskriptif merupakan pisau yang kami gunakan dalam penelitian ini guna memahami secara mendalam bagaimana institusi pemerintah, institusi sosial, dan ruang-ruang publik terlibat dalam pendidikan karakter, serta dampak yang ditimbulkan dalam membentuk nilai-nilai karakter yang positif dalam masyarakat. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur seperti jurnal serta analisis dokumen untuk menggali perspektif berbagai pemangku kepentingan dalam implementasi bentuk pendidikan karakter di masyarakat. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih baik tentang pentingnya peran institusi pemerintah, institusi sosial, dan ruang-ruang publik dalam membentuk karakter yang baik dalam masyarakat. Penelitian ini menggarisbawahi pentingnya peran aktif institusi pemerintah, institusi sosial, dan ruang-ruang publik dalam membentuk karakter yang baik dalam masyarakat. Hasil penelitian diharapkan memberikan pemahaman mendalam tentang dampak positif yang dapat dihasilkan oleh keterlibatan aktif dari pihak-pihak tersebut. Dengan demikian, penelitian ini bertujuan untuk mengisi kesenjangan pengetahuan terkait implementasi pendidikan karakter berbasis masyarakat. Simpulan penelitian ini mencerminkan urgensi peran bersama pemerintah, institusi sosial, dan ruang-ruang publik dalam membentuk nilai-nilai karakter yang positif, yang pada gilirannya dapat meningkatkan kualitas hidup masyarakat secara keseluruhan.